Statistical analysis and prediction of the construction demand of smart elderly care - Zhu, Junyi; Sun, Jingyi; Chen, Zhiyuan (Transactions on Economics, Business and Management Research, 2024)
China is facing a severe problem of population aging, and the number of elderly population is large and continues to grow. Under the current social background, the acceptance of new technology products among the elderly shows a steady increasing trend. From the perspective of empirical research, the popularization of new technology products has become one of the important indicators to measure the modern living level of the elderly. In addition, with the general improvement of education level and the diversification of information access channels, the cognitive ability and learning willingness of the elderly for new technology products have been significantly enhanced.